Potential the Black Soldier Fly (Hermetia illucens) in Feed Formulation for Growth of Common Carp (Cyprinus carpio L.) - Ayu Azkiyah Azizah; Arning Wilujeng Ekawati; Happy Nursyam (Research Journal of Life Science, 2020)
The utilization of maggot as larvae from black soldier fly is an alternative substitution of fish meal as the primary protein source in fish feed. Maggot is cultivated in 3 different cultivation, the medium used is organic waste, tofu waste, and wheat pollard. The method that used in this research is Completely Randomized Design (CRD) with 3 treatments and 3 replication. This study aims to determine the effect of various types of maggot growth media, 1) with maggot biomass parameters, containers, and growing media conditions maggot, 2) then, exact proximate composition, total amino acids content of the prepupae samples were determined. Based on the results of the analysis, each dose of treatment (media) has an influence on the different maggot biomass. The best media treatment results are pollard flour. The proximate analysis showed that BSF larvae had a protein content of 50,88% and also fat content of 15%.